Accessible by design: Applying UDL principles in a first year undergraduate course - Kumar, Kari Lynne; Wideman, Maureen (Canadian Journal of Higher Education, 2014)
This article presents a case study of a technology-enhanced face-to-face health sciences course in which the principles of Universal Design for Learning (UDL) were applied. Students were offered a variety of means of representation, engagement, and expression throughout the course, and were surveyed and interviewed at the end of the term to identify how the UDL-inspired course attributes influenced their perceptions of course accessibility. Students responded very positively to the course design, and felt that the weaving of UDL throughout the course resulted in increased flexibility, social presence, reduced stress, and enhanced success. Overall, students felt more in control of their own learning process and empowered to make personal choices to best support their own learning. This course design also led to increased satisfaction from the perspective of the instructor and reduced the need for intervention by the campus disability services department.